2020
DOI: 10.3390/ijerph17186784
|View full text |Cite
|
Sign up to set email alerts
|

Positive Adolescent Development: Effects of a Psychosocial Intervention Program in a Rural Setting

Abstract: The Positive Youth Development (PYD) approach identifies adolescents as resources to be empowered rather than problems to be solved. All adolescents have strengths and will fully develop when these strengths are integrated with healthy resources in the diverse environments where they live and interact. The objective of this study was twofold: (1) to present the Positive Development Program for Adolescents living in rural areas (DPAR Program) and (2) to pilot test the intervention program. The DPAR program was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Socio-emotional assets make it possible to manage tasks in life, such as controlling impulsivity, problem-solving, and caring about oneself and others (Paricio et al, 2020). Play has a vital role in social skills, self-regulation, and cognitions in children (Hartzell et al, 2020; Savina, 2014).…”
Section: Social–emotional Assets and Resiliencementioning
confidence: 99%
“…Socio-emotional assets make it possible to manage tasks in life, such as controlling impulsivity, problem-solving, and caring about oneself and others (Paricio et al, 2020). Play has a vital role in social skills, self-regulation, and cognitions in children (Hartzell et al, 2020; Savina, 2014).…”
Section: Social–emotional Assets and Resiliencementioning
confidence: 99%
“…Hemos visto que, a pesar de que en la adolescencia existe una tendencia hacia la disminución de las relaciones sociales y a la implicación y participación en los centros educativos, es posible fomentar un entorno positivo en los centros educativos a través de la implementación de programas de Desarrollo Positivo de la Adolescencia, de acceso universal (Oliva et al, 2011;Paricio et al, 2020;Pertegal et al, 2010) que favorezcan la vinculación del alumnado con el centro y promocione su continuidad escolar. Además, la literatura demuestra la importancia de dotar de competencias a los/las adolescentes para garantizar su tránsito exitoso a la vida adulta.…”
Section: Conclusionesunclassified
“…Commonly evaluated outcomes in these programs include psychosocial skills (e.g., self-awareness, emotional management, family relationships) as well as negative and problematic behaviours (e.g., psychological distress, criminality, substance use; Catalano et al, 2004;Curran & Wexler, 2017;Taylor et al, 2017). Prior studies also examined the impacts of PYD programs on diverse outcomes such as grade point average (Benson et al, 2011;Paricio et al, 2020), communication skills (Paricio et al, 2020;Shek & Sun, 2013), critical thinking and problem-solving skills (Johnson et al, 2007;Madsen et al, 2011), teacher-reported goal-setting and social reasoning (Frey et al, 2005), as well as physical activity and meaningful participation in school (Madsen et al, 2011).…”
Section: Pyd Programs In Schoolsmentioning
confidence: 99%